Registers of pressure ulcers in an international context - Andrea Pokorná; Simona Saibertová; Soňa Vasmanská; Lucie Kubátová; Nina Müllerová; Petra Camprová; Gabriela Šmelková (University of Ostrava, 2016)
Aim: The aim of the following review was to search for existing registers of pressure ulcer (PU) incidence operating and collecting data on national level. Design: Type of study - review. Methods: Articles focusing on the subject of national PU registers were searched for by means of a systematic trawl through various databases using relevant terms. The search was limited to articles in English issued between 2010 and 2015 in the electronic databases SCOPUS and Nursing OVID. Articles focused on local datasets or registry as a part of local electronic health records were not included as well as studies which do not describe the dataset or the usability of data collection. Results: In total, six papers were found fulfilling the established criteria. Conclusion: According to information available from the literature review, it was recognised that only one register of PUs currently exists at the national level - the Registry of Ulcer Treatment (RUT) in Sweden. It can be assumed that registers exist in other countries, but that the information is not available on electronic databases. After a detailed inspection of the articles, it appears the information derived from the studies could provide a useful picture of the data that should be collected, and at what time during the treatment period (initial and final assessment of the patients and local symptomatology of the wound/pressure ulcer) it should be collected.